Small signal microwave amplifier design - Grosch, Theodore 1957- (Noble Publishing Corp., 1999)
This book focuses on analytical methods of high-frequency amplifier design by determining the characteristics of input and output networks and their subsequent synthesis. These techniques are combined into a methodology for designing narrowband, small signal amplifiers at RF and microwave frequencies. Applying these techniques facilitates the follow-on stages of modeling and testing the amplifier.